Menelusuri Kualifas Karakter dan Kompetensi Pemimpin Kristen Yang Signifikan - Sambeta, Jenie Aurensia Clara; Mawikere, Marde Christian Stenly; Gara, Johann Nicolaas (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to explore the characteristics and competencies that distinguish significant Christian leaders in facing the dynamics of modern society. A qualitative method was chosen with a focus on analyzing relevant literature studies, allowing for in-depth exploration of these characteristics and competencies. The results of the study indicate that the meaningful character and competency of Christian leaders are not only dependent on leadership skills but also on strong spiritual principles. Fellowship with God, humility, and integrity serve as indispensable foundations in confronting various challenges. Furthermore, clear vision, courage, team-building abilities, resilience, and willingness to continue learning are crucial elements that shape effective Christian leaders. In conclusion, meaningful Christian leaders are not merely leaders but also servants who demonstrate love and serve as living witnesses to God's love for the world. Thus, this research provides a profound understanding of the importance of character and competency in Christian leadership in addressing the challenges of the times